Three-phase unidirectional transformerless hybrid rectifier with boost converter - Gonçalves, José; Valtchev, Stanimir; Melício, Rui; Al-Saadi, Mohammed (IEEE Global Power, Energy and Communication Conference — GPECOM2019, 2019)
In this paper, a three-phase hybrid rectifier is proposed, employing a boost converter without the addition of isolation transformer and output voltage control. This topology is usually considered to be not viable due to the current interactions. In order to mitigate those interactions, the boost inductor is replaced by a magnetically coupled inductor. The coupled inductor forces the balance between the two interconnected windings, placed at the positive and negative poles, and thus eliminating the current interactions. The results show that the proposed three-phase rectifier does not undergo a current interaction and functions as a hybrid rectifier. Furthermore, it was noted that the proposed rectifier at 20 kW presents an elevated power factor and a low total harmonic distortion.
Keywords: Hybrid Rectifier; Coupled Inductor; Boost Converter; Power Factor; Total Harmonic Distortion